PENERAPAN GOOD CORPORATE GOVERNANCE SEBAGAI UPAYA PENINGKATAN KINERJA DAN KEBERLANJUTAN PERUSAHAAN DI INDONESIA - Syahrul Tanjung; Nanda Meyshinta; Amelia Sri Ningsih; Aditya Kurniawan; Ahmad Wahyudi Zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the implementation of Good Corporate Governance (GCG) as an effort to enhance corporate performance and sustainability in Indonesia. The research employs a qualitative approach using a literature review method by examining various written sources, including academic journals, books, research reports, and relevant official documents related to corporate governance. The findings indicate that the consistent application of GCG principles—namely transparency, accountability, responsibility, independence, and fairness—plays a strategic role in strengthening corporate governance systems. Effective GCG implementation improves the quality of managerial decision-making, reinforces internal control mechanisms, and increases stakeholder trust, which positively affects both financial and non-financial corporate performance. However, the implementation of GCG in Indonesia still faces several challenges, such as weak law enforcement, organizational cultures that do not fully support good governance practices, and the dominance of certain interests within corporate ownership structures. Therefore, the success of GCG implementation requires strong commitment from top management, internalization of governance values within corporate culture, and active regulatory oversight to ensure sustainable and competitive corporate development.